A study of anhysteretic remanent magnetization with the variation of A. C. and D. C. fields on Rajmahal basalts (MAUSAM, 1977)
Anhysteretic Remanent Magnetization is produced in a rock specimen when an alternating field, sufficient to cause saturation. is applied and reduced to zero in the presence of a constant direct field. The ARM produced increase with the increase of A. C. field range when the D. C. field is kept constant and reaches a saturation value. The saturation value is different for different specimens and increases as the coercive force increases. The ARM developed in various specimens with the variation of D. C. field, when the maximum alternating field intensity is constant, is a linear function of a small D.C. field.